Dechlorination of Hexachloroethane in Water Using Iron Shavings and Amended Iron Shavings: Kinetics and Pathways. (30th June 2014) - Wu, D. L.; Liu, Y. X.; Liu, Z. G.; Ma, L. M.
Abstract : In contrast to previous studies which employed zero-valent iron powder, this paper investigated reductive dechlorination of hexachloroethane (HCA) using iron shavings and bimetallic iron shavings modified with Cu, Ag, or Pd. Results clearly show that iron shavings offer superior reductive dechlorination of HCA. In addition, surface-normalized pseudo first-order dechlorination rates of 0.0073 L·m −2 ·h −1, 0.0136 L·m −2 ·h −1, 0.0189 L·m −2 ·h −1, and 0.0084 L·m −2 ·h −1 were observed in the presence of iron shavings (Fe 0 ) and the bimetallic iron shavings Cu/Fe, Ag/Fe, and Pd/Fe, respectively. Bimetallic iron shavings consisting of Cu/Fe and Ag/Fe could greatly enhance the reductive reaction rate; Pd/Fe was used to achieve complete dechlorination of HCA within 5 hours. The additives of Ag and Pd shifted product distributions, and the reductive dechlorination of HCA occurred via β reductive elimination and sequential hydrogenolysis in the presence of all iron shavings. This study consequently designed a reaction pathway diagram which reflected the reaction pathway and most prevalent dechlorination products. Iron shavings are a common byproduct of mechanical processing plants. While the purity of such Fe metals may be low, these shavings are readily available at low costs and could potentially be used in engineering applications such as contamination control technologies.